2012
DOI: 10.1186/1756-8722-5-74
|View full text |Cite
|
Sign up to set email alerts
|

Alternative expression of TCRζ related genes in patients with chronic myeloid leukemia

Abstract: A previous study has demonstrated a significant decrease in the TCRζ gene expression level in chronic myeloid leukemia (CML); thus, we further investigated the expression of TCRζ-regulating factors, the distribution of the TCRζ 3' untranslated region (3'-UTR) splice variants, and the expression level and correlation of the alternative splicing factor/splicing factor 2 (ASF/SF-2), FcεRIγ and ZAP-70 genes. TCRζ 3'-UTR splice variants were identified in peripheral blood mononuclear cells (PBMCs) from 14 healthy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
1
23
1
Order By: Relevance
“…Such deficiency in CD3 gene expression levels might be, at least, a part of the reason for the reduction in T cell activation in AML. Similar findings were also reported in CML, CLL, and lymphomas (Huang et al, 2012;Zha et al, 2012b;Liao et al, 2014). Therefore, enhancing CD3 expression may reactive the T cell activation functions and reverse the immunodeficiency in leukemia patients.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Such deficiency in CD3 gene expression levels might be, at least, a part of the reason for the reduction in T cell activation in AML. Similar findings were also reported in CML, CLL, and lymphomas (Huang et al, 2012;Zha et al, 2012b;Liao et al, 2014). Therefore, enhancing CD3 expression may reactive the T cell activation functions and reverse the immunodeficiency in leukemia patients.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, enhancing CD3 expression may reactive the T cell activation functions and reverse the immunodeficiency in leukemia patients. Enhancement in TCRz (CD3z), which is crucial for TCR signaling functions, because it provides 6 of 10 immunoreceptor tyrosine-based activation motifs for the TCR-CD3 complex (Call and Wucherpfennig, 2005;Li, 2008;Zha et al, 2012a), was reported by different methods, including cytokine induction and TCRz transfer in T cells of CML patients (Chen et al, 2009;Zha et al, 2012b). A previous study showed that IL-2 could enhance the TCRf level, but it could not completely recover the TCRf level in T cells in CML patients (Chen et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific amplification of the PCR products was confirmed by melting curve analysis. The data are presented as the relative expression of the genes of interest compared with the internal control gene as determined by the 2( -DCT ) method (Zha et al, 2012;Shi et al, 2013).…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…CML patients have significantly lower numbers of circulating myeloid and plasmacytoid dendritic cells (pDCs) compared with healthy volunteers [8,9]. Bcr/abl1-presenting DCs have been detected in the peripheral blood of CML patients, suggesting that CML-derived DCs may contribute to anti-leukemic immunity [10,11]. Bcr/abl1-presenting DCs can be generated from peripheral blood mononuclear cells (PBMCs) or CD34c progenitor cells of CML patients, and have been shown to have the capacity to capture, process and present bcr/abl1 antigen [5,12].…”
Section: Introductionmentioning
confidence: 99%